Faster Horses, Older Whiskey, and More Money: An Analysis of Religious Influence on Referenda Voting - SATTERTHWAITE, SHAD (Journal for the scientific study of religion, 2005)
This note replicates a previous study to determine the extent religion influences voting behavior. It focuses on ballot measures that involve moral issues and considers other factors as well. A multiple regression uses the percentage of voters favoring five ballot proposals as the dependent variable, with socioeconomic status, rural isolation, liquor consumption, and three categories of religion as independent variables. The analysis revealed that the religion variables were significant and negatively associated with voting for most proposals that liberalized drinking and betting. Socioeconomic status and liquor consumption were significant in most cases and were positively linked to votes cast for the proposals.